Scalable Cloud-based ETL for Self-serving Analytics - Zdravevski, Eftim; Apanowicz, Cas; Stencel, Krzysztof; Slezak, Dominik (My University, 2019)
Nowadays, companies must inevitably analyze the available data and extract meaningful knowledge. As an essential prerequisite, Extract-Transform-Load (ETL) requires significant effort, especially for Big Data. The existing solutions fail to formalize, integrate and evaluate the ETL process for Big Data in a scalable and cost-effective way. In this paper, we introduce a cloud-based architecture for data fusion and aggregation from a variety of sources. We identify three scenarios that generalize data aggregation during ETL. They are particularly valuable in the context of machine learning, as they facilitate feature engineering even in complex cases when the data from an extended time period has to be processed. In our experiments, we investigate user logs collected with Kinesis streams on Amazon AWS Hadoop clusters and demonstrate the scalability of our solution. The considered datasets range from 30 GB to 2.5 TB. The results were deployed in the domains, such as churn prediction, fraud detection, service outage prediction, and more generally – decision support and recommendation systems.
Keywords: Data warehouses, Data streams, ETL, Business analytics